2012
DOI: 10.4007/annals.2012.175.2.3
|View full text |Cite
|
Sign up to set email alerts
|

The Möbius function is strongly orthogonal to nilsequences

Abstract: We show that the Möbius function µ(n) is strongly asymptotically orthogonal to any polynomial nilsequence (F (g(n)Γ)) n∈N . Here, G is a simply-connected nilpotent Lie group with a discrete and cocompact subgroup Γ (so G/Γ is a nilmanifold ), g : Z → G is a polynomial sequence, andIn particular, this implies the Möbius and Nilsequence conjecture MN(s) from our earlier paper for every positive integer s. This is one of two major ingredients in our programme to establish a large number of cases of the generalise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
290
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(296 citation statements)
references
References 14 publications
6
290
0
Order By: Relevance
“…[5, §1.5.2] for a discussion; compare also p. 3 below). Recently, however, some new important cases have been established: Green and Tao [15] have proved effective equidistribution of polynomial orbits on nilmanifolds; this is an important input in their work on linear equations in primes [14], [16]. Moreover, Einsiedler, Margulis and Venkatesh [5] have proved effective equidistribution for large closed orbits of semisimple groups on homogeneous spaces; see also Mohammadi [34] for a more explicit result in the special case of closed SO(2, 1)-orbits in SL(3, Z)\ SL (3, R).…”
Section: Introductionmentioning
confidence: 99%
“…[5, §1.5.2] for a discussion; compare also p. 3 below). Recently, however, some new important cases have been established: Green and Tao [15] have proved effective equidistribution of polynomial orbits on nilmanifolds; this is an important input in their work on linear equations in primes [14], [16]. Moreover, Einsiedler, Margulis and Venkatesh [5] have proved effective equidistribution for large closed orbits of semisimple groups on homogeneous spaces; see also Mohammadi [34] for a more explicit result in the special case of closed SO(2, 1)-orbits in SL(3, Z)\ SL (3, R).…”
Section: Introductionmentioning
confidence: 99%
“…This sum measures the correlation between µ(n) and the constant function. Recent studies have explored the correlation between µ(n) and other sequences, see [5,2,1]. Sarnak [8] showed that µ(n) does not correlate with any "deterministic" (i. e., zero entropy) sequence, assuming an old conjecture of Chowla [3] on the auto-correlation of the Möbius function, which asserts that given an r-tuple of distinct integers α 1 , .…”
Section: Introductionmentioning
confidence: 99%
“…In numerous cases, this conjecture has recently been proved to hold: [1], [3], [4], [9], [16], [19], [21] (see also [25]). …”
Section: Consider Now X = O(x) ⊂ {0 1}mentioning
confidence: 99%